Body surface area equations for physically active men and women. Issue 2 (26th October 2022) - Looney, David P.; Potter, Adam W.; Arcidiacono, Danielle M.; Santee, William R.; Friedl, Karl E.
Abstract: Objectives: To improve predictive formulae for estimating body surface area (BSA) in healthy men and women using a modern three‐dimensional scanner technology. Methods: Body surface areas were obtained from a convenience sample of 1267 US Marines (464 women and 803 men) using a whole body surface scanner (Size Stream SS20). The reliability of SS20 measures of total and regional BSA within participants was compared across triplicate scans. We then derived a series of formulae to estimate SS20‐measured BSA using various combinations of sex, height, and mass. We also assessed relationships between percent body fat measured by dual‐energy x‐ray absorptiometry and sex‐specific formulae errors in Marines. Results: Body surface areas recorded by the SS20 were highly reliable whether measured for the total body or by region (ICC ≥ .962). Formulae estimates of BSA from sex, height, and mass were precise (root‐mean‐square deviation, 0.031 m 2 ). Errors from the Marine Corps formulae were positively associated with percent body fat for men ( p  = .001) but not women ( p  = .843). Conclusions: Clinicians, military leaders, and researchers can use the newly developed BSA formulae for precise estimates in healthy physically active men and women. Users should be aware that height‐ and mass‐based BSA estimates are less accurate for individuals with extremely low or high percent body fat.